Effects of Parenting Stress and Depressive Symptoms on Children's Internalizing and Externalizing Problems. - Lim, Sun Ah; Shim, Sook Young (Journal of Child & Family Studies, 2021)
This study explored how parenting stress can affect depressive symptoms in parents, between parents, and, ultimately, their children's internalizing and externalizing problems. First, we examined the relationship between parenting stress and depressive symptoms in mothers and fathers. Second, we examined the mutual influence of fathers' and mothers' parenting stress and depressive symptoms on the marital couple. Last, we examined the effect of the mutual influence of parenting stress and depressive symptoms on the child's internalizing and externalizing problems. To this end, we analyzed the data of 1,358 participants in Years 5–7 (2012–2014) from the Panel Study on Korean Children (PSKC), employing the actor-partner independence model and structural equation modeling. The results indicated that parenting stress was associated with depressive symptoms in both parents, which then exerted an effect on their children's internalizing and externalizing problems. Furthermore, parents' depressive symptoms mediated a positive relationship between parenting stress and children's internalizing and externalizing problems. Our findings demonstrate the importance of the mutual influence of both parents' stress and depressive symptoms on children's internalizing and externalizing problems. Highlights: Children in early childhood were extremely susceptible to the internal characteristics of their parents. One parent's parenting stress was associated with his/her own depressive symptoms as well as the depressive symptoms of his/her spouse. The mutual relationship of stress and depressive symptoms in both parents was associated with the child's internalizing and externalizing problems.